Keep it real: selecting realistic sets of urban green space indicators. (17th August 2020) - Carmen, Raïsa; Jacobs, Sander; Leone, Michael; Palliwoda, Julia; Pinto, Luís; Misiune, Ieva; Priess, Jörg A; Pereira, Paulo; Wanner, Saskia; Ferreira, Carla Sofia; Ferreira, António
Abstract: With increasing urbanisation, urban green spaces are expected to be crucial for urban resilience and sustainability, through the delivery of ecological, economic and social benefits. In practice, however, planning, management and evaluation of urban green spaces are rarely structured and evidence-based. This represents a missed opportunity to account for, track and foster the multiple benefits that green spaces are expected to deliver. To gain insight into this gap, this study assesses the availability and uptake of relevant evidence by city governments. Interviews, focus groups and quantitative surveys were applied in four medium-sized European cities: Coimbra (Portugal), Genk (Belgium), Leipzig (Germany), and Vilnius (Lithuania), covering the main governance and climatic gradients in Europe. Using straightforward data exploration and regression, we analyse which ecological, economic and social indicators are typically chosen by cities and why. Together with the city stakeholders, we derived a common set of benefit categories and key performance indicators which can be adapted to diverse local contexts. We conclude that cities tend to make pragmatic decisions when composing their indicator sets, but nevertheless cover multiple urban green space dimensions. Finally, we explore how indicator choice could be optimised towards a complementary and credible indicator set, taking into account a realistically feasible monitoring effort undertaken by the cities.